Antibacterial activity of nifuratel in urine and serum. Issue 5 (May 1972) - McGeachie, J.; Robinson, G.; Black, D.
Abstract : The minimum inhibitory concentrations of nifuratel for 205 randomly selected isolates from urinary tract infections were tested by tube dilution. Of these, 177 (86·3%) were resistant to more than 6 μg/ml and 140 of 141 (99·3%) strains of Escherichia coli were resistant to more than 3 μg/ml. Urine levels of nifuratel were examined in two groups: one group had 400 mg given once and the other group had 2 g given over 24 hours. In both groups samples of urine were collected every hour for seven hours after the last dose. After one 400-mg dose the maximum urine level achieved by any subject was 2·0 μg/ml and the mean maximum level was 0·75 μg/ml. With the 2 g total dose, the maximum level noted was 4 μg/ml and the mean maximum level was 1·8 μg/ml. No measurable inhibition was noted in any of the blood samples removed at one and a half to two hours after the last dose.